Distrusting community health workers with confidential health information: a convergent mixed-methods study in Swaziland. Issue 6 (12th April 2017) - Geldsetzer, Pascal; Vaikath, Maria; De Neve, Jan-Walter; Bossert, Thomas J; Sibandze, Sibusiso; Mkhwanazi, Mandla; Bärnighausen, Till
Abstract: Background Patients are unlikely to share the personal information that is critical for effective healthcare, if they do not trust that this information will remain confidential. Trust in confidentiality may be particularly low in interactions with community health workers (CHW) because CHW deliver healthcare outside the clinic setting. This study aims to determine the proportion of Swaziland's population that does not trust the national CHW cadre with confidential medical information, and to identify reasons for distrust. Methods Using two-stage cluster random sampling, we carried out a household survey covering 2000 households across 100 census enumeration areas in two of Swaziland's four regions. To confirm and explain the quantitative survey results, we used qualitative data from 19 semi-structured focus group discussions in the same population. Results 49% of household survey participants stated that they distrust the national CHW cadre with confidential health information. Having ever been visited by a CHW was positively associated with trust (aOR: 2.11; P  < 0.001), while higher levels of schooling of the respondent were negatively associated (aOR for more than secondary schooling versus no schooling: 0.21; P  < 0.001). The following three primary reasons for distrusting CHW with confidential health information emerged in the qualitative analyses: (1) CHW are members of the same community as their clients and may thus share information with people who know the client, (2) CHW are mostly women and several focus group participants assumed that women are more likely than men to share information with other community members, and (3) CHW are not sufficiently trained in confidentiality issues. Conclusion Our findings suggest that confidentiality concerns could be a significant obstacle to the successful rollout of CHW services for stigmatized conditions in Swaziland. Increasing coverage of the CHW program, raising the population's confidence in CHWs' training, assigning CHW to work in communities other than the ones in which they live, changing the CHW gender composition, and addressing gender biases may all increase trust with regards to confidentiality.